2022
DOI: 10.3390/ijms23031681
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Tomato Phytochrome A and B1B2 Mutants in Response to Heat Stress

Abstract: Heat stress (HS) is a prevalent negative factor affecting plant growth and development, as it is predominant worldwide and threatens agriculture on a large scale. PHYTOCHROMES (PHYs) are photoreceptors that control plant growth and development, and the stress signaling response partially interferes with their activity. PHYA, B1, and B2 are the most well-known PHY types in tomatoes. Our study aimed to identify the role of tomato ‘Money Maker’ phyA and phyB1B2 mutants in stable and fluctuating high temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…Several studies have shown that PHYs also respond to other abiotic stresses. Mutations in tomato PHYA and a double mutation in PHYB1B2 increased tolerance toward heat stress by inhibiting electrolyte leakage (EL) and enhancing several stress-responsive genes [ 18 ]. Moreover, a mutation in PHYB decreases the EL index and malondialdehyde (MDA) concentration and enhances cold tolerance in rice plants [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that PHYs also respond to other abiotic stresses. Mutations in tomato PHYA and a double mutation in PHYB1B2 increased tolerance toward heat stress by inhibiting electrolyte leakage (EL) and enhancing several stress-responsive genes [ 18 ]. Moreover, a mutation in PHYB decreases the EL index and malondialdehyde (MDA) concentration and enhances cold tolerance in rice plants [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stomata facilitate gas and water exchange between plants and the surrounding environment [ 44 ], and lower stomatal conductance was often linked with a lower net photosynthetic rate [ 45 ]. CO 2 used for photosynthesis was acquired through the stomata opening [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both iaa9-3 and iaa9-5 mutants have higher chlorophyll fluorescence under normal and heat stress conditions ( Figure 6 ). Higher chlorophyll fluorescence of both iaa9-3 and iaa9-5 can be attributed to lower MDA content ( Figure 5 ), which indicates less leaf oxidative damages [ 44 ], higher leaf chlorophyll and carotenoid contents, which helps prevent photo-oxidative stress [ 55 ], and higher stomatal conductance which prevents Fq/Fm reduction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the targets could be PHTOCHROME (PHY). PHYB has been identified as a thermosensor [ 84 , 85 ], and the phy mutant exhibited high tolerance to heat stress in Arabidopsis [ 86 ] and tomato [ 87 ]. This mutant information is important for the definition of targets of genome editing.…”
Section: Abiotic Stress Responses Revealed By Genome Editingmentioning
confidence: 99%